Implementing of Science-Social Integration in Islamic Education Learning - Wahyu Hidayat; Tatang Ibrahim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2021)
Theoretically, religion and social science have an integrative relationship because they originate from God developed by human. However, practically, the relationship occurs in a dichotomy so that it has implications in learning activities at Islamic educational institutions, especially in the classroom context. The gap between those theories and practice generates the idea of integrating religious science and social science in Islamic universities. Therefore, this article describes the implementation of social science in Islamic religious education learning at the Department of Islamic Education State Islamic University of Sunan Gunung Djati Bandung. Based on the theory of scientific integration, this study applied observation, interviews, and documentation techniques. The result shows that social science can be integrated into Islamic education learning related to learning (philosophical) competencies, learning materials, learning strategy; and the learning evaluation.